2018
DOI: 10.1007/s40843-017-9210-1
|View full text |Cite
|
Sign up to set email alerts
|

High-performance of sodium carboxylate-derived materials for electrochemical energy storage

Abstract: , respectively. With these superior electrochemical properties, the sodium carboxylate-derived materials could be considered as promising organic electrode materials for large-scale sustainable lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The preparation of electrode sheet and the assembly process of battery are similar with that of our published work (Chen et al, 2016b;Xu et al, 2018Xu et al, , 2019Zhu et al, 2018;Xiao et al, 2019), as shown in Scheme 2. PAN organic carbon powder, super P (SP), and poly(vinylidene fluoride) (PVDF) binder were mixed in a ratio of 85:10:5 by weight, and 35 mL of N-methylpyrrolidone (NMP) solvent was added to 4 g of this mixture.…”
Section: Preparation Of Electrode Sheet and Batterymentioning
confidence: 56%
See 1 more Smart Citation
“…The preparation of electrode sheet and the assembly process of battery are similar with that of our published work (Chen et al, 2016b;Xu et al, 2018Xu et al, , 2019Zhu et al, 2018;Xiao et al, 2019), as shown in Scheme 2. PAN organic carbon powder, super P (SP), and poly(vinylidene fluoride) (PVDF) binder were mixed in a ratio of 85:10:5 by weight, and 35 mL of N-methylpyrrolidone (NMP) solvent was added to 4 g of this mixture.…”
Section: Preparation Of Electrode Sheet and Batterymentioning
confidence: 56%
“…Among all the components of lithium-ion battery, electrode materials are the key factors that restrict the performance of lithium-ion batteries. Among them, negative electrode material, as an important part of lithium ion battery, has an important influence on the electrochemical performance of lithium ion battery (Chen et al, 2016a,b;Wang et al, 2017;Maruyama et al, 2018;Xu et al, 2018Xu et al, , 2019Zhu et al, 2018;Xiao et al, 2019). In lithium ion battery anode material, carbon material has the advantages of low electrode potential, high cycle efficiency, long cycle life, and good safety performance, makes it the preferred anode material for lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70][71][72] It's worth mentioning that the opportunities of organic cathodes will be greater along with the development of ether-based electrolyte, in that ether-based electrolyte can better restrict the dissolution of active organic molecules. [73][74][75] Beyond conventional sodium-ion batteries, sodium-sulfur and sodium-oxygen batteries also witness fruitful advancement with ether-based electrolytes in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…have attracted much attention as a class of emerging electrochemical energy storage materials. [14][15][16][17][18][19][20] Although small molecules of oxygen-containing conjugated organic anode materials can obtain high discharge capacity, 17,21 most of them show poor cycling performance and rate performance due to the following factors. [22][23][24] Firstly, organic electrode substances (especially organic materials with a small molecular weight) may be dissolved in electrolyte during cycling, resulting in poor cycle stability; secondly, small molecules are easily aggregated to limit the exposed active sites, resulting in low capacity and coulomb efficiency; Thirdly, organic electrode materials usually show low conductivity, resulting in poor rate performance.…”
Section: Introductionmentioning
confidence: 99%